Effective Dose of Nano Propolis as Anti-Pain in Animal Models of Mus Musculus Using Writhing Test Method - Witjaksana, Annisa Salsabila; Widjiastuti, Ira; Juniarti, Devi Eka (Universitas Airlangga, 2023)
Background: Odontogenic pain has a high prevalence where this pain is the result of noxious physical stimuli or calming inflammatory mediators that stimulate receptors located at the terminal ends of nociceptive C and AÎ´ afferent nerve fibers. Nano propolis is an alternative material that is used as a medicine in dentistry. Nano propolis is a mixture of natural resins containing flavonoids and phenolic acids which play a role in suppressing pain response through COX and NF-kB inhibition mechanisms. Nanoparticle technology is capable of preparing active drug ingredients in nano-sized particles and can affect drug effectiveness, because particle size affects the process of solubility, absorption and distribution of drugs. Research on the potential of nano propolis as an anti-pain is still minimal, so further research is needed on the function of nano propolis as an alternative anti-pain agent. Purpose: To determine the effective dose of nano propolis on pain response in Mus musculus. Methods: This research was conducted using the writhing test method to see the analgesic effect of nano propolis. The research sample consisted of 28 Mus musculus which were divided into four treatment groups, namely the piroxicam control group, and the nano propolis treatment group of 17.5 mg/kg, 35 mg/kg, and 70 mg/kg. Results: The results showed that the four treatment groups did not have a significant difference, in other words, they had the same anti-pain effect. Conclusion: Nano propolis 35 mg/kgBB is an effective dose in suppressing pain response in Mus musculus.